Archaeometallurgical record as tool to preserve architectural heritage information in Malaga, Spain - Hernández-Escampa, Marco; Barrera-Fernández, Daniel; Menchaca-Campos, Carmina; Uruchurtu-Chavarín, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work approaches views on the preservation of industrial housing heritage in Malaga, Spain, and the pressure caused by its recent urban renovation. The aims of the research include geographic space analysis and assessing how archaeological recording and archaeometry, specifically archaeometallurgy, can contribute to the preservation of information about structures and materials that continuously disappear from urban contexts. The results constitute an initial beginning to expand a comparative archaeological database for the city. The ideas and procedures presented here are expected to provide some guidance for generating further research from urban, architectural, archaeological, and geographical perspectives.